2022
DOI: 10.20525/ijrbs.v11i9.2091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of disclosure of public sector financial information on quality of financial reporting in public secondary schools in Kakamega County, Kenya

Abstract: The objective of this study was to determine the effect of public sector financial information disclosure on the quality of financial reporting in public secondary schools in Kakamega County. This study was premised on a theoretical foundation based on legitimacy theory. The study employed a descriptive research design. The study targeted 419 public secondary schools, from which a sample of 205 public secondary schools was obtained using a stratified random sampling technique. The study used Primary data, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A market survey on ALV, found that in three markets in Western Kenya, vegetables included cowpea leaves, pigweed, African nightshades, jute mallow, spiderplant, slenderleaf, African kale, and pumpkin leaves (Abukutsa-Onyango et al, 2003). Indeche found that over 50 percent of the women farmers grew African nightshade, cowpea leaves, slenderleaf, jute mallow and spider plant (Indeche, 2015). These were also the most common ALV in the markets.…”
Section: Utilizationmentioning
confidence: 99%
“…A market survey on ALV, found that in three markets in Western Kenya, vegetables included cowpea leaves, pigweed, African nightshades, jute mallow, spiderplant, slenderleaf, African kale, and pumpkin leaves (Abukutsa-Onyango et al, 2003). Indeche found that over 50 percent of the women farmers grew African nightshade, cowpea leaves, slenderleaf, jute mallow and spider plant (Indeche, 2015). These were also the most common ALV in the markets.…”
Section: Utilizationmentioning
confidence: 99%